2014
DOI: 10.4161/21645515.2014.980202
|View full text |Cite
|
Sign up to set email alerts
|

Regional variations in HPV vaccination among 9–17 year old adolescent females from the BRFSS, 2008–2010

Abstract: Human papillomavirus (HPV) vaccine uptake among 18-26 y old women varies by geographic region in the US. However, little is known about regional variations in vaccination among girls who are in the vaccine's targeted age groups. Regional variation in HPV vaccination among female adolescents (9-17 y old) was examined using crosssectional data from the Behavioral Risk Factor Surveillance System (BRFSS) between 2008 and 2010. Multivariable logistic regression estimated the association of region of residence (10 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 18 publications
0
12
1
Order By: Relevance
“…Regional variation in the uptake of recommendations on a number of health interventions has previously been documented. 29,30 Additionally, Sourik Sarkar and coauthors found significant regional variability in hepatitis C testing. 28 Taken together, these findings suggest the need for region-specific programs to augment guidelines to further improve screening.…”
Section: Discussionmentioning
confidence: 99%
“…Regional variation in the uptake of recommendations on a number of health interventions has previously been documented. 29,30 Additionally, Sourik Sarkar and coauthors found significant regional variability in hepatitis C testing. 28 Taken together, these findings suggest the need for region-specific programs to augment guidelines to further improve screening.…”
Section: Discussionmentioning
confidence: 99%
“…The Southern states, in particular, have had lower HPV vaccination rates compared to other regions of the US. 14 In 2008-2010, adolescents in the South and Southwestern states were less likely to initiate the HPV vaccine series compared to states in the rest of the US. 14,15 More recent data of 13-17 year olds showed that adolescents in the Western US states were more likely to have been vaccinated than those in the South.…”
Section: Hpv Vaccination Disparitiesmentioning
confidence: 99%
“…14 In 2008-2010, adolescents in the South and Southwestern states were less likely to initiate the HPV vaccine series compared to states in the rest of the US. 14,15 More recent data of 13-17 year olds showed that adolescents in the Western US states were more likely to have been vaccinated than those in the South. 83 Unfortunately, many Southern states in the US also have high rates of cervical cancer.…”
Section: Hpv Vaccination Disparitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This diversity is reflected in the variation of vaccination rates across states and regions with Northeastern, Midwestern, and Western states seeing higher rates of HPV vaccination coverage than Southern and Southwestern. 2,4,5 Several studies have attempted to demonstrate the impact of state policies on vaccine uptake; focusing on particular states and specific policies such as HPV vaccine school-entry requirements [6][7][8] or policies requiring vaccine education for parents. 8,9 As observed by Durham et al, 10 and Roberts et al, 11 variability in HPV vaccine uptake across the United States is probably a function, at least in part, of a collection of structural elements, such as law and policy.…”
Section: Introductionmentioning
confidence: 99%